Reputation as a Key Resource for Market Success in the Banking Sector (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Acknowledging the importance and role of corporate reputation as a unique intangible and specific organizational resource, in this paper, we analyze its role and importance for the market success of contemporary banks. Furthermore, the paper provides an overview of the existing research regarding bank reputation in the Republic of Croatia. As corporate social responsibility aspect of a business is one of the most widely studied aspects of corporate reputation, we investigate the corporate social responsibility practice of two major banks in Croatia. By using publicly available data, we analyse the internal and external dimensions of their CSR and their relation to a bank’s reputation.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.